Differential Effect of Sex on Mortality According to Age in Heart Failure - Yoonpyo Lee; Minjae Yoon; Dong‐Ju Choi; Jin Joo Park (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Heart failure exhibits sex‐based differences in prevalence, clinical characteristics, and outcomes. However, these differences may have an interaction with age. This study investigates these disparities in Asian patients with acute heart failure according to age. Methods and Results We pooled data from the KorHF (Korea Heart Failure) and the KorAHF (Korean Acute Heart Failure) registries including 3200 patients between 2005 and 2009 and 5625 patients between 2011 and 2014, respectively, hospitalized for acute heart failure in Korea. Patients were categorized by their age into 2 groups: those with age ≥70 years and those with age <70 years. The primary endpoint was in‐hospital and postdischarge outcomes according to sex, stratified by age. Of 8825 patients, 45.7% had an age <70 years, and 54.3% had an age ≥70 years. Women were older on average in both groups. Differences in baseline characteristics were more apparent in the older group, with women having a higher prevalence of hypertension and valvular heart disease, whereas more men had chronic kidney disease, previous myocardial infarction, chronic obstructive pulmonary disease, and strokes. Both in‐hospital and postdischarge mortalities showed differences only in the older group, with men dying more (5.08% versus 7.41%, P<0.001; 17.95% versus 22.20%, P<0.001 respectively). This pattern persisted to adjusted analyses, which revealed that men have a 54% (odds ratio, 1.54 [95% CI, 1.17–2.04]) and 30% (hazard ratio, 1.30 [95% CI, 1.13–1.51]) increased in‐hospital and 1‐year mortality, respectively, compared with women. Conclusions In patients hospitalized with acute heart failure, male sex is an independent predictor of mortality in older patients but not younger patients.